Entropy generation and thermoeconomic analysis of printed circuit heat exchanger using different materials for supercritical CO2 based waste heat recovery. (2020) - Manjunath, K.; Sharma, O.P.; Kaushik, S.C.
Abstract: This article presents the entropy generation and thermoeconomic performance analysis of printed circuit heat exchanger (PCHE) using different materials of construction-based heat recovery heat exchanger (HRHE) for emerging waste heat recovery system (WHRS) utilising the marine gas turbine exhaust as the heat source and supercritical CO2 as working fluid. The mathematical model for the efficient yet compact PCHE based HRHE has been developed keeping in mind severe footprint, volume and weight restrictions for waste heat recovery in shipboard. The parametric and thermoeconomic analyses of the proposed HRHE using the second law performance parameters such as entropy generation number, rational efficiency, thermoeconomic cost and heat exchanger fabrication materials properties has been presented. The influence of variations in topping engine load on geometrical parameters of HRHE is carried out considering hastealloy-N and stainless-steel materials and the optimized values are presented that lowers the heat transfer and pressure drop irreversibilities. It is found that, at low load operations, the thermoeconomic cost, which is combination of capital cost and the irreversibility penalty costs decreases and the second law efficiency increases. Although using hastealloy-N as heat exchanger fabrication material is costlier compared to stainless steel, but its second law efficiency value increases.